Pengembangan Media Lift The Flap Book pada Mata Pelajaran IPAS Materi Tumbuhan, Sumber Kehidupan di Bumi untuk Peserta Didik Kelas IV SDN 1 Wajak Lor Boyolangu Tulungagung - Yurida Salsabela; Nourma Oktaviarini (Journal on Education, 2024)
As time goes by, science is increasingly developing, one of which is in subjects in elementary school, namely Natural and Social Sciences. Through social science learning media, it is hoped that students will be able to develop curiosity about their environment. One of the supporting factors is the use of graphic learning media. The purpose of this research is to develop creative and interesting graphic media in the form of a lift-the-flap book. The lift the flap book medium is a learning medium that presents two different page views that encourage readers to pause, look, and wonder. This research method is development research (RnD) with the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The instruments used in this study are questionnaires, interviews, and documentation. The results obtained from the validation of media experts were 93.75%, and material experts obtained 92.5%. The questionnaire and interview assessment were carried out on grade IV students of SDN 1 Wajak Lor, which amounted to 18 students, obtaining 98.75%. The results of this study show that the lift the flap book medium in the science and science subject of plant material, the source of life on earth, for grade IV students of SDN 1 Wajak Lor is very valid and suitable to be used as a learning medium in the classroom.